1968
DOI: 10.3109/00365516809167062
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Growth-Mediated Changes in Hemodynamics and Tubular Transport of Sodium, Glucose and Hippurate after Nephrectomy

Abstract: BUGGE-ASPERHEIM, B. & KIIL, F. Examination of Growth-Mediated Changes in Hemodynamics and Tubular Transport of Sodium, Glucose and Hippurate after Nephrectomy. Scand. J. din. Lab. Invest. 22, 255-265, 1968.Mitotic activity in renal cortical tubules of dogs was not significantly different from controls after peritoneal drainage of one of the kidneys, but increased more than five-fold after nephrectomy. In order to examine which functional changes were growth-mediated, clearance studies were performed on four un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

1972
1972
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
2
7
0
1
Order By: Relevance
“…Glucose Tn" as a proximal tubular func tion believed to vary mainly with mass of the kidney, was increased by 2-4 days, with an apparently maximum increase attained by 1-2 weeks [60]. In another study, however, no change in glucose Tm was seen at I week but a 37% increase by 15 and a 50% increase by 30 days were reported [73]. PAH Tm in these same studies increased by 70%.…”
Section: Crg In Dogsmentioning
confidence: 70%
See 2 more Smart Citations
“…Glucose Tn" as a proximal tubular func tion believed to vary mainly with mass of the kidney, was increased by 2-4 days, with an apparently maximum increase attained by 1-2 weeks [60]. In another study, however, no change in glucose Tm was seen at I week but a 37% increase by 15 and a 50% increase by 30 days were reported [73]. PAH Tm in these same studies increased by 70%.…”
Section: Crg In Dogsmentioning
confidence: 70%
“…Unilateral ureteral ligation, abruptly eliminating the function of one kidney, resulted in contralateral hypertrophy which was initially much slower than that following UNX and indicated that lost renal mass per se was at least partially responsible for growth. Return to the body of the output of one kidney in rats and dogs by way of ureteral diversion to duodenum [53,54], peritoneal space [73,150,154,264,336,458,472,500] or vena cava [145,353] also is the functional equiva lent of ureteral ligation or UNX. This doubling of the load has no effect on the size of either organ or on DN A synthesis [458] or Na/K-ATPase concentration [150].…”
Section: Excretory Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PAH and glucose transport are augmented after uni nephrectomy [4,5] and changes in renal sodium handling occur [6][7][8][9][10][11]. However, the findings concerning renal so dium handling postuninephrectomy are not consistent.…”
Section: Introductionmentioning
confidence: 76%
“…This tailoring of filtering and reabsorptive capacities in each nephron for nu merous solutes was emphasized by Smith [40] and was called glomerular-tubular bal ance. After removal of most of the kidney mass, GTB for sodium and water applies immediately for the remaining nephrons be fore any mitotic activity has started, but tubular growth signified by increased capac ity for glucose reabsorption requires several weeks to develop [6], How glomerular and tubular growth processes are coordinated remains unknown. Evidently glomerulartubular balance is a prerequisite for measur ing GTB in the whole kidney.…”
Section: Regulation Of Proximal Tubular Reabsorption Of Naclmentioning
confidence: 99%